Uji Tumbuh Kapang Aspergillus niger pada Beberapa Media Bahan Pangan Asal Sulawesi Utara - Meiske Naomi Mamuaja; Dokri Gumolung (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The development of functional food today mainly focuses on founding food that rich in nutrition and also provide health benefit for human consumption. At this point the combination of prebiotic and probiotic food that refer to food with health benefit to help digestible function become increasing. This research was done by literature study and laboratory experiment with 5 medium and 4 replications in order to found the possibility to produce fructooligosaccharide from Aspergillus niger fermentation in some typical foodstuffs from North Sulawesi i.e pisang goroho (Musa acuminate), sweet potato (Ipomeae batatas), coconut water, and palm sugar. Statistical analysis of the results shown that the Aspergillus niger tend to grow in 4 of 5 medium which indicate the possibility of fructooligosaccharide in those medium. Further studies are needed in order to know the production of fructooligossaccharide based on its medium.